2017
DOI: 10.3389/fmicb.2017.01721
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Tract As Entry Route for Hantavirus Infection

Abstract: Background: Hantaviruses are zoonotic agents that cause hemorrhagic fevers and are thought to be transmitted to humans by exposure to aerosolized excreta of infected rodents. Puumala virus (PUUV) is the predominant endemic hantavirus in Europe. A large proportion of PUUV-infected patients suffer from gastrointestinal symptoms of unclear origin. In this study we demonstrate that PUUV infection can occur via the alimentary tract.Methods: We investigated susceptibility of the human small intestinal epithelium for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 26 publications
6
24
0
3
Order By: Relevance
“…In fact, viral enrichment was often found in the vicinity of perinuclear microtubule aggregates (Figure 7B, Figure S8). Both observations support previous reports about the importance of the cytoskeleton in hantavirus infections (4, 27). Of note, other virus families have been previously reported to stimulate endocytosis pathways and in particular macropinocytosis in order to facilitate their uptake and productive entry into host cell (28, 29).…”
Section: Resultssupporting
confidence: 92%
“…In fact, viral enrichment was often found in the vicinity of perinuclear microtubule aggregates (Figure 7B, Figure S8). Both observations support previous reports about the importance of the cytoskeleton in hantavirus infections (4, 27). Of note, other virus families have been previously reported to stimulate endocytosis pathways and in particular macropinocytosis in order to facilitate their uptake and productive entry into host cell (28, 29).…”
Section: Resultssupporting
confidence: 92%
“…When transmitted to humans, hantaviruses can cause severe disease. Transmission occurs usually through inhalation of aerosolized rodent excreta and rarely via biting by infected animals [ 18 ], but the human intestinal tract is a possible entrance port, too [ 19 ]. Hantaviruses present on the American continent, such as SNV or Andes virus (ANDV) cause hantavirus (cardio)pulmonary syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we screened by RT‐PCR samples of urine and faeces (from all captured bats), lungs, liver and heart tissues from tested bats, but we failed to find any positives. Although the digestive tract is not a normal infection route by hantavirus, recently, a study showed that cells from the gastrointestinal tract could be infected and maintains Puumala orthohantavirus (Witkowski et al, ). Therefore, we also tested samples of saliva from all captured bats and intestine from the tested bats, but, again, we failed to find any positive sample, even from those bats serologic positive.…”
Section: Resultsmentioning
confidence: 99%